Seventeenth-Century Poetic Genres as Social Categories : a New Reading of the Poetry of John Donne. - Takseva, Tatjana (Edwin Mellen Press, 2010)
Through the reading records of Donne?s poems and the concept of multiple referentiality, this study examines the social dimensions of early modern genres and the relationship among poetics, rhetoric and the Renaissance doctrines of imitation, placing systematic attention on how the differences oral and written modes of expression influences the process of reading and the early modern understanding of genre.